Peran PKK Dalam Meningkatkan Pemahaman Nilai-Nilai Islam Ibu-ibu di Desa Gelebak Dalam Kabupaten Banyuasin - Renasya Miftahul Jannah; Hidayatullah (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "The Role of PKK in Improving the Understanding of Islamic Values of Mothers in Gelebak Dalam Village, Banyuasin Regency". The purpose of this research is to find out the role of PKK in improving the understanding of Islamic values, especially mothers in Gelebak Dalam Village, Banyuasin Regency, and to find out the supporting factors and inhibiting factors. This research used a type of field research with qualitative methods. The data sources used are primary data and secondary data. Data collection techniques in this research are observation, interview, and documentation. The location of this research is Gelebak Dalam Village, Rambutan District, Banyuasin Regency. The theory used is the Jim Ife-Frank Tesoriero theory which explains the role of facilitative roles, educational roles, representational roles, technical roles. As well as using Nurchilish Madjid's opinion about Islamic values which are the core of religion. The results of this study are the role of PKK in helping to improve understanding of Islamic values, especially mothers in Gelebak Dalam village, through facilitating roles, educational roles, representational roles, technical roles. The programs are specifically made to increase understanding of Islamic values, especially, the values of Iman, Islam, Ihsan, Taqwa, Ikhlas, Tawakkal, and Gratitude. Mothers who take part in existing programs can strengthen the relationship between each other, get inner peace, increase knowledge that previously did not know to know, then increase devotion to Allah SWT. PKK's supporting factors in increasing the understanding of Islamic values of mothers are: human resources, facilities and infrastructure while the inhibiting factors are: time, lack of funds and different levels of understanding